Response of the level 1 circuits for tension changes: consumption and losses (2002)
This article presents a methodology that seeks to estimate the behavior of the demand of residential users and the losses in the network in face of the voltage changes of Level I '. Starting from the characterization of the consumption of household appliances, as a function of the service voltage, a general method is applied that allows to obtain a better approximation to the behavior of the load, compared to the models currently used.